Konsumsi minyak ikan lele (Clarias gariepinus) yang diperkaya omega 3 memperbaiki low density lipoprotein (LDL) dan kolesterol total pada lansia - Srimiati, Mia; Kusharto, Clara Meliyanti; Tanziha, Ikeu; Suseno, Sugeng Heri (Jurnal Gizi dan Pangan, 2017)
The objective of this study was to analyze the effect of catfish oil supplementation on the LDL and total cholesterol levels in the elderly. Experimental design with randomized controlled trial (RCT) was  used in this study. Subjects were divided into two groups, the first group (A1) was given catfish oil 1,000 mg per day, while the second group (A2) was not given the oil, it was called a control. The lipid profile measurement was performed before and after the intervention. Catfish oil consumed daily by treatment group for 60 days and then the effect on the lipid profile was evaluated. Total cholesterol and LDL in the two groups did not differ significantly. However, total cholesterol and LDL cholesterol of the treatment group had lower scores than the control group. In addition, the LDL levels in the treatment group were below maximum level, or maybe normal. The LDL and total cholesterol in the control group increased significantly (p<0.05), while in the treatment group was not significant. It might be due to enhancement of the consumption of the subject for 60 days. Thus, catfish oil enriched with omega 3 could inhibit the rate of enhancement of the LDL and total cholesterol.